2009
DOI: 10.1103/physrevb.80.113403
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium kinetics of a disordered Luttinger liquid

Abstract: We develop a kinetic theory for strongly correlated disordered one-dimensional electron systems out of equilibrium, within the Luttinger liquid model. In the absence of inhomogeneities, the model exhibits no relaxation to equilibrium. We derive kinetic equations for electron and plasmon distribution functions in the presence of impurities and calculate the equilibration rate γE. Remarkably, for not too low temperature and bias voltage, γE is given by the elastic backscattering rate, independent of the strength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In long samples the conductance is not observed to be quantized [7] indicating that backscattering processes occur between the counterpropagating edge channels. It was found that in the limit eV k B T the resistance is independent on temperature between 20 mK -4.2 K and it increases linearly with the edge length L. These observations are not surprising once the elastic backscattering processes are allowed and large voltage is applied, because under these conditions the inelastic scattering rate is expected to be approximately equal to the elastic one [33], and therefore the localization effects can be neglected and the resistance is expected to be temperature independent. In the QSH phase the elastic backscattering is forbidden in the presence of time-reversal symmetry due to the topological protection, so these observations are not consistent with the system being in the QSH phase without additional assumption about the existence of charge puddles that may lead to enhanced backscattering rate [34].…”
Section: Length Temperature and Voltage Dependence Of The Conductancementioning
confidence: 95%
“…In long samples the conductance is not observed to be quantized [7] indicating that backscattering processes occur between the counterpropagating edge channels. It was found that in the limit eV k B T the resistance is independent on temperature between 20 mK -4.2 K and it increases linearly with the edge length L. These observations are not surprising once the elastic backscattering processes are allowed and large voltage is applied, because under these conditions the inelastic scattering rate is expected to be approximately equal to the elastic one [33], and therefore the localization effects can be neglected and the resistance is expected to be temperature independent. In the QSH phase the elastic backscattering is forbidden in the presence of time-reversal symmetry due to the topological protection, so these observations are not consistent with the system being in the QSH phase without additional assumption about the existence of charge puddles that may lead to enhanced backscattering rate [34].…”
Section: Length Temperature and Voltage Dependence Of The Conductancementioning
confidence: 95%
“…Defining signatures of a LL such as spin-charge separation [6,7], charge fractionalization [8,9], and the power-law suppression of the local electron tunneling density of states [10,11,12,13,14] have been experimentally verified. Recently, LLs driven far from equilibrium have begun to receive attention [15,16,17,18]. Studying these systems offers the possibility to characterize novel aspects of electron-electron interactions and to understand energy relaxation processes that have not been apparent in the above-mentioned equilibrium experiments.…”
mentioning
confidence: 99%
“…In long samples, the conductance is not observed to be quantized [7], indicating that backscattering processes occur between the counterpropagating edge channels. It was found that in the limit eV k B T , the resistance is independent on temperature between 20 mK-4.2 K and it increases linearly with the edge length L. These observations are not surprising once the elastic backscattering processes are allowed and large voltage is applied, because under these conditions the inelastic scattering rate is expected to be approximately equal to the elastic one [35] and therefore the localization effects can be neglected and the resistance is expected to be temperature independent. In the QSH phase, the elastic backscattering is forbidden in the presence of TRS due to the topological protection, so these observations are not consistent with the system being in the QSH phase without additional assumptions about the existence of charge puddles that may lead to enhanced backscattering rate [36].…”
Section: Length Temperature and Voltage Dependence Of The Conductancementioning
confidence: 96%